Pengembangan Aplikasi Flood Disaster Untuk Meningkatkan Pengetahuan Mitigasi Bencana Banjir Pada Anak Usia 5-6 Tahun Di Tk Satu Atap 021 Kabupaten Indragiri Hilir - Nurhayati Harahap; Yeni Solfiah; Ria Novianti (Departement of Mathematics Education, 2024)
This study aims to develop the Flood Disaster application to increase knowledge of flood disaster mitigation in children aged 5-6 years in One Roof 021 Kindergarten, Indragiri Hilir Regency. The type of research used is RND (Research and Developmet) research with quantitative methods. The steps used are six stages, namely potential and problems, data collection, product design, design validation, design revision, product trials. The data analysis technique used is quantitative descriptive. The results of the study obtained media expert validation of 93.53%, material expert validation of 91% and educator experts of 91.86% with a very feasible category. The results of the limited trial conducted were obtained at 86% with the Very Feasible category. From the results of the study, it is concluded that the Flood Disaster application is feasible to use as a medium to increase knowledge of flood disaster mitigation in children aged 5-6 years in One Roof Kindergarten 021 Indragiri Hilir Regency.